The Precarious in the Cinemas of the Americas - Felman-Panagotacos, Madison (Imagofagia, 2021)
Sobre Constanza Burucúa y Carolina Sitnisky. The Precarious in the Cinemas of the Americas. Cham: Palgrave Macmillan, 2018, 301 pp., ISBN: 978-3-319-76806-9.